2011
DOI: 10.1097/iae.0b013e318205b228
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment With Intravitreal Injection of Ranibizumab and Reduced Fluence Photodynamic Therapy for Choroidal Neovascularization Secondary to Angioid Streaks

Abstract: The preliminary results of this prospective study indicate that combination treatment with intravitreal ranibizumab injection and reduced fluence photodynamic therapy for choroidal neovascularization associated with angioid streaks seems to be effective in reducing or eliminating retinal edema, regression of neovascularization, and improving or stabilizing visual acuity without any complications. Large controlled studies are needed to evaluate the long-term effects of this combination regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Treatment options have included laser photocoagulation, photodynamic therapy, and intravitreal anti-vascular endothelial growth factor drugs 5,9,11,13. The latter are the only ones that have proven to be able to induce visual stabilization or increase visual acuity up to 3 years after onset of the treatment 11,14.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment options have included laser photocoagulation, photodynamic therapy, and intravitreal anti-vascular endothelial growth factor drugs 5,9,11,13. The latter are the only ones that have proven to be able to induce visual stabilization or increase visual acuity up to 3 years after onset of the treatment 11,14.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging anatomical results were achieved in all studies except one [24] , and these studies report a reduction or at least a stabilization of the central retinal thickness measured by optical coherence tomography (OCT) [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] . It was also shown that combination therapies do not yield better results than monotherapy [28,[42][43][44] . At present, in chronically active AS-related CNV, the available treatments do not prevent the functional loss but rather limit it [23,45] .…”
Section: Introductionmentioning
confidence: 99%
“…This observation has been confirmed in long-term studies with follow-up times exceeding one year, that report recurrent or newly developed CNV in different regions in half of the study cohorts 17,18,27. The use of intravitreal ranibizumab (Lucentis ® , Genetech Inc), the antigen-binding fragment of recombinant, humanized monoclonal antibody that neutralizes all active forms of VEGF A, was also used in CNV-related angioid streaks with promising results 32. The largest published retrospective case series investigating the use of ranibizumab in CNV secondary to angioid streaks demonstrated a stabilization of visual acuity over 24 months with a mean of 5.7 injections 27…”
Section: Discussionmentioning
confidence: 78%